2012
DOI: 10.5455/jeim.280812.or.043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biomarkers for the detection of hepatocellular carcinoma in patients with hepatitis C virus

Abstract: Objective: Hepatocellular carcinoma (HCC) is the most frequent and severe complication of chronic liver diseases. It represents an important public health problem in Egypt, where up to 90% of HCC cases are attributable to hepatitis C virus (HCV) infection. The objective of the present study was to assess a panel of biomarkers that can significantly differentiate between HCC and non-HCC patients with chronic HCV infection (CHC), quantitatively. Methods: A total of 75 adult male patients with CHC were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…The present study showed that there was a highly significant increase in serum ALP activity in the HCC group when compared to control group and untreated HCV infected group P<0.001, but There was a non significant increase in serum ALP activity in the untreated HCV infected group when compared to control group P = 0.249. This was in agreement with that reported by Sleisenger and Fordtran [32] and Morcos et al [1] who found that the conventional tests of hepatic function don't distinguish hepatocellular carcinoma from other hepatic masses or from cirrhosis. In this study there is a significant increase in serum total bilirubin in the HCC groups compared to control group, but showing non significantly variations between HCC group and HCV group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study showed that there was a highly significant increase in serum ALP activity in the HCC group when compared to control group and untreated HCV infected group P<0.001, but There was a non significant increase in serum ALP activity in the untreated HCV infected group when compared to control group P = 0.249. This was in agreement with that reported by Sleisenger and Fordtran [32] and Morcos et al [1] who found that the conventional tests of hepatic function don't distinguish hepatocellular carcinoma from other hepatic masses or from cirrhosis. In this study there is a significant increase in serum total bilirubin in the HCC groups compared to control group, but showing non significantly variations between HCC group and HCV group.…”
Section: Discussionsupporting
confidence: 93%
“…The burden of Hepatocellular carcinoma (HCC) has been increasing in Egypt with a doubling in the incidence rate in the past 10 years [1]. Early diagnosis of HCC is of great importance in order to offer the possibility of curative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…At a cut-off value of 1.92, the AST/ALT ratio was postulated by Morcos et al 31 to give the best sensitivity (83%) and specificity (71%) in differentiating HCC from patients with cirrhosis in their study done on 75 patients.…”
Section: Discussionmentioning
confidence: 99%
“…A weakness of this meta-analysis is the limited number of studies included. Also the meta-analysis could not be extended to other HCC markers, such as P53 (35), interleukins (41), osteopontin (34), talin I (36), lipocalin (37) and others (38–3940, 42) due to the limited number of studies made on these markers. Of course, this meta-analysis had some limitations.…”
Section: Discussionmentioning
confidence: 99%